Sinematografi Pelatihan Pembuatan Film Bersama Teater Matan dan Mahasiswa FIB Unilak: Indonesia - Evizariza Evi; M. Kafrawi (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2021)
In this modern era marked by the discovery of advanced technology, it requires a creative young generation, so that they can compete in accordance with the demands of the times. One of the areas of creativity that gets that place is creativity in creating films. Films can be used as a place to express feelings, as well as be used as a product promotion or area where the film's work is produced. This fact is strengthened by the increasing inclusion of social media such as YouTube, Facebook, Twitter, and Instagram which provide video media in their content. To produce good film work requires a process of putting into practice the theories of filmmaking. With this film-making training, at least the members of the Matan Theater can get to know more closely what film is and can practice making good and correct films at the same time.